The everything learning Spanish book : speak, write, and understand basic Spanish in no time - Gutin, Julie (Everything series., 2007)
A comprehensive guide with accompanying audio CD that provides the basic techniques for learning the Spanish language including the alphabet and pronunciation, everyday words and phrases, asking common questions, and grammar.